Footloose labour working in India's informal economy - Breman, Jan 1936- (Contemporary South Asia, 1996)
In a penetrating anthropological study of the working poor in India, Jan Breman examines the lives of those who, pushed out of the agrarian labour market, depend on casual work. Beginning his local-level research in two villages in south Gujarat, the author discusses the mobilisation of casual labour, which is hired and fired according to the need of the moment, and transferred for the duration of the job to destinations far away from the home area. His case-study reveals that the circulation of labour is indicative of an employment pattern which dominates both the rural and urban economy of large parts of South Asia. Elaborating on the social profile of the work migrants, the author argues that their identity is shaped by both class and caste relations and, despite action by state agencies, nothing of significance has been achieved to improve their quality of life